Benefits of the two-way immersion program into language environment in the conditions of trilingual education of Kazakhstan - Zhetpisbaeva, B.А.; Ospanova, A.K.; Dyakov, D.V. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
Authors considered one of the relevant methods of training of foreign languages — the program of two-way immersion into language environment. In the article theoretical aspects of the two-way immersion program into language environment are considered, in particular determination of the essence of the concept and criterions of success of implementation of this program in the educational sphere. This analysis allowed authors to define advantages of the usage of the two-way immersion program into language environment, its focus on development of children’s language competences, improvement of quality of knowledge of the second language in addition to the first or native language; formation of the secondary language personality, capable to carry out successful social interaction with other culture. Finally, authors make a conclusion that this program is effective in the field of foreign-language education and can be successfully realized in the system of trilingual education of Kazakhstan.
Қазақстанда үштілді білім беру аясында тілдік ортаға бірегей ену бағдарламасының артықшылықтары
Преимущества программы двустороннего погружения в языковую среду в условиях трехъязычного образования Казахстана
Keywords: trilingual education; immersion into language; two-way immersion program into language environment; two-way immersion